The role and mechanism of histone lactylation in health and diseases - Xie, Yumei; Hu, Hongxia; Liu, Maoting; Zhou, Tingting; Cheng, Xi; Huang, Wei; Cao, Ling (Frontiers in Genetics, 2022)
Lactate is produced during glycolysis under anaerobic or aerobic environments. Increasing evidence has indicated that lactate is not only an important metabolite to bridge glycolysis and oxidative phosphorylation, but also act as a multifunctional signaling molecule developing non-metabolic functions. Histone post-translational modifications (HPTMs) are crucial epigenetic mechanisms regulating various biological events. With the application of mass spectrometry (MS)-based proteomics, novel HPTMs have been successively discovered. Recently, histone lactylation modification mediated by lactate have been found, and further studies showed that it was involved in tumorigenesis, inflammation, lung fibrosis, and so on, indicating its significant role in immune regulation and maintenance of homeostasis. This review provides an overview of histone lactylation modification and a glimpse into their complex regulation in pathological even physiological conditions.